Bismuth-doped optical fiber and preparation method thereof

Through repeated soaking and baking treatment, the concentration of Bi-related active centers in bismuth-doped fibers is improved, and the problem of low concentration of bismuth-doped centers in existing bismuth-doped fibers is solved, and the preparation cost and difficulty is reduced. It is suitable for high-efficiency fiber communication systems.

CN118405842BActive Publication Date: 2025-03-04WUHAN CHANGJIN PHOTONICS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410717550.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2025-03-04
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

The concentration of bismuth active centers in existing bismuth-doped fibers is low, which leads to a significant increase in the cost of gain fibers and device production difficulty when used in bismuth-doped fiber amplifiers when used for a long length, which hinders the practicality of bismuth-doped fibers.

Method used

By repeatedly soaking the quartz reaction tube containing a loose layer in an ionic solution containing Bi3+ and baking treatment at different temperatures and gas environments, Bi3+ is fixed and SiO2 loose layer is deposited to increase the concentration of Bi-related activity centers.

Benefits of technology

The concentration of Bi-related active centers in bismuth-doped fibers is significantly improved, and the cost and difficulty of fiber preparation is reduced, making bismuth-doped fibers more suitable for efficient fiber communication systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118405842B_ABST
    Figure CN118405842B_ABST
Patent Text Reader

Abstract

The present invention provides a bismuth-doped optical fiber and a preparation method thereof, the method comprising: immersing a quartz reaction tube containing a loose layer in a bismuth-doped optical fiber. 3+ The quartz reaction tube is baked under a first mixed gas to obtain a first dry quartz tube, wherein the first mixed gas includes a mixed gas of silicon tetrachloride, oxygen and chlorine; the first dry quartz tube is immersed in a Bi-containing 3+ The first dried quartz tube is baked in a second mixed gas to obtain a second dried quartz tube, wherein the second mixed gas includes a mixed gas of oxygen and chlorine; the second dried quartz tube is subjected to a vitrification, sintering and drawing process, namely, a bismuth-doped optical fiber; the present invention combines repeated immersion of Bi 3+ The process and corresponding parameter optimization have greatly increased the concentration of Bi-related active centers in bismuth-doped optical fibers without changing or upgrading the existing MCVD conventional preparation conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optical fiber technology, and in particular to a bismuth-doped optical fiber and a preparation method thereof. Background Art

[0002] With the rapid development and iterative upgrade of ultra-high-definition video, mobile networks, smart travel, big data, cloud computing and 5G technology, my country's data traffic has increased by more than 1,000 times compared to 10 years ago, which poses a major challenge to large-capacity transmission optical fiber communication systems. There are three main solutions to the capacity crisis in existing optical fiber systems: 1. Increase the single-channel transmission rate; 2. Reduce the channel spacing; 3. Expand the transmission bandwidth. In contrast, due to the nonlinear effect of optical fiber, expanding the transmission bandwidth is currently the most compatible, lowest cost and most effective method. Bismuth-doped optical fiber has ultra-wideband near-infrared luminescence characteristics. In bismuth-doped optical fibers of different matrices, its gain range can cover the entire low-loss transmission window of quartz optical fiber. However, due to the unknown formation mechanism and source of the luminescent active centers (i.e., effective luminescent gain ions) of bismuth-doped optical fibers, the concentration of effective active bismuth ions in optical fibers is low (<100ppm), which makes the length of bismuth-doped optical fibers used in bismuth-doped fiber amplifiers (BGDFs) as long as 80m to 320m, compared with the 5-10m optical fiber used in current commercial EDFAs. The cost of gain optical fibers and the difficulty of device manufacturing have increased exponentially, seriously hindering the practical application of bismuth-doped optical fibers. Therefore, it is of great significance to study methods to increase the concentration of bismuth active centers in bismuth-doped optical fibers.

[0003] However, the main method for preparing bismuth-doped optical fibers is currently MCVD (modified chemical vapor deposition, in which the raw materials to be reacted are carried into the substrate tube from the air inlet end of the substrate tube using oxygen as a carrier gas, and heated by a burner outside the substrate tube to indirectly heat the reaction raw materials in the substrate tube to produce a glass body, which is deposited on the inner wall of the substrate tube). Bismuth compounds (mainly BiCl3, with a boiling point of about 447°C) volatilize severely during the preparation process at a temperature of up to 2000~2300°C, and a large amount of Bi elements escape from the reaction tube, resulting in extremely low bismuth active center content in the final prepared bismuth-doped optical fiber. How to achieve a significant increase in the bismuth active center content in bismuth-doped optical fibers poses a huge challenge to the process control parameters in MCVD. Summary of the invention

[0004] The object of the present invention is to provide a bismuth-doped optical fiber and a preparation method thereof, so as to improve the technical problem of low bismuth active center concentration in the bismuth-doped optical fiber of the prior art.

[0005] In order to solve the above technical problems, the present invention provides a method for preparing bismuth-doped optical fiber, comprising:

[0006] S10, immersing the quartz reaction tube containing the loose layer in a Bi 3+In the first ion solution;

[0007] S20, baking the quartz reaction tube under a first mixed gas to obtain a first dry quartz tube, wherein the first mixed gas includes a mixed gas of silicon tetrachloride, oxygen and chlorine;

[0008] S30, immersing the first dried quartz tube in a Bi-containing 3+ in a second ion solution;

[0009] S40, baking the first dried quartz tube under a second mixed gas to obtain a second dried quartz tube, wherein the second mixed gas includes a mixed gas of oxygen and chlorine;

[0010] S50, performing vitrification, sintering and drawing treatments on the second dried quartz tube to obtain a bismuth-doped optical fiber.

[0011] Preferably, in step S10, the immersion time is 1 to 4 hours, the solvent of the first ion solution is deionized water or anhydrous ethanol, and the solute includes at least Bi 3+ , Bi in the first ion solution 3+ The concentration is 0.2~0.6mol / L.

[0012] Preferably, in step S20, the quartz reaction tube is baked using an oxyhydrogen lamp at a baking temperature of 900-1400° C. The moving direction of the oxyhydrogen lamp is the same as the flow direction of the first mixed gas in the quartz reaction tube.

[0013] Preferably, in step S20, the first mixed gas is a mixed gas consisting of silicon tetrachloride, oxygen, helium, nitrogen and chlorine; the flow rate of chlorine in the first mixed gas is greater than 0 and less than or equal to 200 Sccm, and the flow rate of silicon tetrachloride is 100~200 Sccm.

[0014] Preferably, in step S30, the immersion time is 1 to 4 hours, the solvent of the second ion solution is deionized water or anhydrous ethanol, and the solute includes at least Bi 3+ , the second ion solution Bi 3+ The concentration is 0.5~1.2mol / L.

[0015] Preferably, in step S40, the first dry quartz tube is baked using an oxyhydrogen lamp at a baking temperature of 800-1000° C. The moving direction of the oxyhydrogen lamp is the same as the flow direction of the second mixed gas in the first dry quartz tube.

[0016] Preferably, the second mixed gas is a mixed gas consisting of oxygen, helium, nitrogen and chlorine; and the flow rate of chlorine in the second mixed gas is greater than 0 and less than or equal to 200 Sccm.

[0017] Preferably, step S50 specifically includes:

[0018] S501, introducing oxygen into the second dried quartz tube to vitrify the inner wall of the second dried quartz tube, and then sintering and shrinking it into a transparent quartz preform rod;

[0019] S502, inserting the quartz preform rod into the sleeve, and drawing it into an optical fiber in a drawing tower, namely, a bismuth-doped optical fiber.

[0020] Preferably, in step S501, the temperature for vitrifying the second dried quartz tube is 1900~2300°C, and the pressure inside the second dried quartz tube during vitrification is 0.6~0.9Torr; the temperature for shrinking the second dried quartz tube is 2000~2200°C, and the pressure inside the second dried quartz tube during shrinking is 0.1~0.3Torr.

[0021] Correspondingly, the present invention also provides a bismuth-doped optical fiber, which is prepared by any of the above methods for preparing a bismuth-doped optical fiber.

[0022] The beneficial effects of the present invention are as follows: Different from the prior art, the present invention provides a bismuth-doped optical fiber and a preparation method thereof, the method comprising: immersing a quartz reaction tube containing a loose layer in a bismuth-doped optical fiber; 3+ The quartz reaction tube is baked under a first mixed gas to obtain a first dry quartz tube, wherein the first mixed gas includes a mixed gas of silicon tetrachloride, oxygen and chlorine; the first dry quartz tube is immersed in a Bi-containing 3+ The first dried quartz tube is baked under a second mixed gas to obtain a second dried quartz tube, wherein the second mixed gas includes a mixed gas of oxygen and chlorine; the second dried quartz tube is subjected to a vitrification, sintering and drawing process, namely, a bismuth-doped optical fiber; the present invention first immerses the quartz reaction tube containing the loose layer in the first ion solution, so that the Bi in the first ion solution 3+ The Bi is then added into the quartz reaction tube through the pores of the loose layer; the quartz reaction tube is then baked. 3+ While being fixed in the quartz reaction tube, an additional loose layer of SiO2 is deposited on the inner wall of the quartz reaction tube through the reaction of silicon tetrachloride and oxygen; then the first dried quartz tube is immersed in the second ion solution, so that the Bi in the second ion solution 3+ The BiO2 is doped into the first dried quartz tube through the pores of the SiO2 loose layer; the first dried quartz tube is then baked to 3+ The bismuth-doped optical fiber is fixed in the first dry quartz tube; finally, the second dry quartz tube is subjected to a vitrification, sintering and drawing process to obtain the bismuth-doped optical fiber; the present invention combines repeated immersion of Bi 3+The process and corresponding parameters are optimized, and the concentration of Bi-related active centers in bismuth-doped optical fibers is greatly increased without changing or upgrading the existing MCVD conventional preparation conditions. This method is extremely suitable for the existing preparation process system. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A flow chart of a method for preparing a bismuth-doped optical fiber provided in an embodiment of the present invention;

[0024] Figure 2 The figure is a comparison diagram of the absorption spectra of the bismuth-doped optical fibers prepared in various embodiments of the present invention and comparative examples. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] See also Figure 1 , Figure 1 A flow chart of a method for preparing a bismuth-doped optical fiber provided in an embodiment of the present invention; the method for preparing the bismuth-doped optical fiber comprises the following steps:

[0027] S10, immersing the quartz reaction tube containing the loose layer in a Bi 3+ in the first ion solution.

[0028] Specifically, S10 also includes:

[0029] First, a loose layer of phosphosilicate material or a loose layer of germanosilicate material is deposited on the inner wall of the quartz reaction tube; wherein the quartz reaction tube refers to a high-purity quartz reaction tube (Heraeus F300), and the purpose of depositing the loose layer of phosphosilicate material or the loose layer of germanosilicate material is mainly to make the subsequent Bi 3+ It is incorporated into the quartz reaction tube through the pores of the loose layer.

[0030] Furthermore, when depositing a loose layer of phosphosilicate material or a loose layer of germanosilicate material, the moving direction of the hydrogen-oxygen lamp is opposite to the gas flow direction in the quartz reaction tube, and the flame temperature is 1300~1600℃ (which is conducive to the loose layer sintering on the inner wall of the quartz reaction tube without falling off).

[0031] Among them, since the feed tube in the MCVD equipment is on the left side of the quartz reaction tube, when the oxyhydrogen lamp moves from left to right (the moving direction of the oxyhydrogen lamp is the same as the gas flow direction in the quartz reaction tube), the oxyhydrogen lamp will heat the deposits on the inner wall of the tube again, which will cause the volatile substances in the deposits to volatilize due to heat, and further cause the deposition amount of volatile substances to fail to meet the design requirements. When the oxyhydrogen lamp moves from right to left (the moving direction of the oxyhydrogen lamp is opposite to the gas flow direction in the quartz reaction tube), the oxyhydrogen lamp will not heat the deposits on the inner wall of the quartz reaction tube again, thereby greatly reducing the thermal volatilization of volatile substances.

[0032] In this embodiment, both phosphosilicate and germanosilicate are volatile substances. Therefore, in this preparation method, the moving direction of the oxyhydrogen lamp in step S10 is set to be opposite to the gas flow direction in the quartz reaction tube (moving from right to left). This can inhibit the volatilization of phosphosilicate and germanosilicate, providing a basis for ensuring the performance of the optical fiber.

[0033] Then, the quartz reaction tube containing the loose layer is immersed in Bi 3+ In the first ion solution, Bi 3+ It is incorporated into the quartz reaction tube through the pores of the loose layer.

[0034] Specifically, in step S10, the immersion time is 1 to 4 hours, the solvent of the first ion solution is deionized water or anhydrous ethanol, and the solute is Bi 3+ Various compounds, the first ion solution Bi 3+ The concentration is 0.2~0.6mol / L.

[0035] S20, baking the quartz reaction tube under a first mixed gas to obtain a first dry quartz tube, wherein the first mixed gas includes a mixed gas of silicon tetrachloride, oxygen and chlorine.

[0036] Specifically, step S20 also includes:

[0037] First, the soaked quartz reaction tube is placed in nitrogen for purging to remove large water droplets in the quartz reaction tube; wherein the nitrogen flow rate is 30-80 Sccm and the purging time is 3-4 hours.

[0038] Afterwards, the quartz reaction tube is placed on a hydrogen-oxygen lamp for high-temperature baking, and at the same time, a certain amount of mixed gas containing silicon tetrachloride, oxygen and chlorine is introduced into the quartz reaction tube.

[0039] Specifically, in step S20, the quartz reaction tube is baked using a hydrogen-oxygen lamp at a baking temperature of 900-1400°C. The moving direction of the hydrogen-oxygen lamp is the same as the flow direction of the first mixed gas in the quartz reaction tube (to make the loose layer condense quickly, which is beneficial to Bi 3+ fixed in the loose layer).

[0040] Specifically, in step S20, the first mixed gas is a mixed gas composed of silicon tetrachloride, oxygen, helium, nitrogen and chlorine; the flow rate of chlorine in the first mixed gas is greater than 0 and less than or equal to 200 Sccm, and the flow rate of silicon tetrachloride is 100~200 Sccm.

[0041] Among them, helium and nitrogen are used as carrier gases to input silicon tetrachloride, oxygen and chlorine into the inner wall of the quartz reaction tube; silicon tetrachloride and oxygen can be deposited on the surface of the loose layer of phosphosilicate material or the loose layer of germanosilicate material through the MCVD process to form a loose layer of SiO2 material, which is beneficial to the subsequent Bi 3+ It is doped into the first dry quartz tube through the pores of the loose layer; the amount of silicon tetrachloride introduced affects the thickness of the loose layer of SiO2 material. If the amount introduced is high, the thickness of the loose layer of SiO2 material is larger, but the Bi ion doping amount has tended to saturation, so the amount of silicon tetrachloride introduced is not the larger the better.

[0042] Furthermore, the present application defines the amount of chlorine gas introduced and the baking temperature, and the flow rate of chlorine gas is greater than 0 and less than or equal to 200 Sccm; the reason is that chlorine gas is a key gas for removing hydroxide (hydroxide is produced by hydrolysis of silicate and some ion solutions contain hydroxide, and the absorption peak of hydroxide is mainly located at about 1385 nm, which coincides with the bismuth-doped optical fiber co-doped with low concentration Ge, which forms a deep depression at 1385 nm in its gain spectrum, thus seriously affecting the amplification performance and gain flatness of the bismuth-doped optical fiber), but it will cause the volatilization of Bi ions. Hydroxyl cannot be eliminated without the introduction of chlorine gas. After too much introduction, the efficiency of hydroxide removal is high, but the Bi ions are volatilized too much. The amount of chlorine gas introduced not only affects the volatilization rate of Bi ions, but also affects the efficiency of hydroxide removal, and both are affected by temperature. The more chlorine gas or the higher the temperature, the faster the Bi ions volatilize, so it is necessary to select a suitable amount of chlorine gas introduced and baking temperature.

[0043] S30, immersing the first dried quartz tube in a Bi-containing 3+ of the second ion solution.

[0044] Specifically, step S30 also includes:

[0045] The first dry quartz tube containing the loose layer of SiO2 material is immersed in a Bi 3+ The second ion solution of Bi 3+ It is incorporated into the first dry quartz tube through the pores of the loose layer of SiO2 material.

[0046] Specifically, in step S30, the immersion time is 1 to 4 hours, the solvent of the second ion solution is deionized water or anhydrous ethanol, and the solute is Bi 3+Various compounds, the second ion solution Bi 3+ The concentration is 0.5~1.2mol / L; among them, the Bi 3+ The concentration is greater than that of the first ion solution. 3+ The purpose of the concentration is to incorporate as much Bi as possible. 3+ (Because the first dried quartz tube has two loose layers, the loose layer of the phosphosilicate material or the loose layer of the germanosilicate material may not completely absorb Bi 3+ ).

[0047] S40, baking the first dried quartz tube under a second mixed gas to obtain a second dried quartz tube, wherein the second mixed gas includes a mixed gas of oxygen and chlorine.

[0048] Specifically, step S40 also includes:

[0049] First, the soaked first dried quartz tube is placed in nitrogen for purging to remove large water droplets in the first dried quartz tube; wherein the nitrogen flow rate is 30-80 Sccm and the purging time is 3-4 hours.

[0050] Afterwards, the first dry quartz tube is placed on a hydrogen-oxygen lamp for low-temperature baking, and at the same time, a certain amount of mixed gas containing oxygen and chlorine is introduced into the first dry quartz tube.

[0051] Specifically, in step S40, the first dry quartz tube is baked using an oxyhydrogen lamp at a baking temperature of 800-1000° C. The moving direction of the oxyhydrogen lamp is the same as the flow direction of the second mixed gas in the first dry quartz tube.

[0052] In this embodiment, the moving direction of the oxyhydrogen lamp in step S40 is set to be the same as the gas flow direction in the quartz reaction tube (moving from left to right), so that the first dry quartz tube can be heated twice, thereby removing moisture and hydroxyl radicals in the first dry quartz tube.

[0053] Specifically, the second mixed gas is a mixed gas consisting of oxygen, helium, nitrogen and chlorine; the flow rate of chlorine in the second mixed gas is greater than 0 and less than or equal to 200 Sccm.

[0054] Among them, helium and nitrogen are used to act as carrier gases to input chlorine gas into the inner wall of the quartz reaction tube, and the chlorine gas is used to remove hydroxide.

[0055] Furthermore, the reason why silicon tetrachloride is not introduced in step S40 is that there are already two loose layers, and re-deposition of the loose layer may easily cause it to fall off.

[0056] Furthermore, the baking temperature in step S40 is lower than the baking temperature in step S20 because the Bi 3+ The concentration is greater than the Bi in the quartz reaction tube in step S10. 3+ concentration, so the baking temperature needs to be lowered to prevent Bi 3+ Volatile.

[0057] S50, performing vitrification, sintering and drawing treatments on the second dried quartz tube to obtain a bismuth-doped optical fiber.

[0058] Specifically, step S50 also includes:

[0059] S501, introducing oxygen into the second dried quartz tube to vitrify the inner wall of the second dried quartz tube, and then sintering and shrinking it into a transparent quartz preform rod;

[0060] S502, inserting the quartz preform rod into the sleeve, and drawing it into an optical fiber in a drawing tower, namely, a bismuth-doped optical fiber.

[0061] Preferably, in step S501, the temperature for vitrifying the second dried quartz tube is 1900~2300°C, and the pressure inside the second dried quartz tube during vitrification is 0.6~0.9Torr; the temperature for shrinking the second dried quartz tube is 2000~2200°C, and the pressure inside the second dried quartz tube during shrinking is 0.1~0.3Torr.

[0062] The technical solution of the present application is now described in conjunction with specific embodiments.

[0063] Embodiment 1:

[0064] Embodiment 1 of the present invention provides a method for preparing a bismuth-doped optical fiber with a high active center concentration, which comprises the following steps:

[0065] Step 1, depositing a loose layer of phosphosilicate or a loose layer of germanosilicate on the inner wall of a quartz reaction tube;

[0066] Step 2: Immerse the quartz reaction tube with the loose layer in a Bi-containing 3+ In the water or ethanol solution of ions, the Bi ion concentration is 0.3 mol / L;

[0067] Step 3: Place the soaked quartz reaction tube in nitrogen and purge it to remove large water droplets in the tube. The nitrogen flow rate is 30 Sccm and the purge time is 4 hours.

[0068] Step 4, placing the quartz reaction tube obtained in step 3 on a hydrogen-oxygen lamp for high-temperature baking, while introducing a certain amount of mixed gas containing silicon tetrachloride, oxygen, helium, nitrogen and chlorine into the tube, while maintaining the pressure in the tube sufficiently high, the baking temperature is 1200-1400°C, and the chlorine flow rate is 100 Sccm;

[0069] Step 5: immerse the quartz reaction tube obtained in step 4 in a Bi-containing 3+ In the water or ethanol solution of ions, the concentration of Bi ions is 0.6 mol / L;

[0070] Step 6: Place the soaked quartz reaction tube in nitrogen and purge it to remove large water droplets in the tube. The nitrogen flow rate is 30 Sccm and the purge time is 4 hours.

[0071] Step 7, placing the quartz reaction tube obtained in step 6 on a hydrogen-oxygen lamp for low-temperature baking, while introducing a certain amount of mixed gas containing oxygen, helium, nitrogen and chlorine into the tube, while maintaining the pressure in the tube sufficiently high, the baking temperature is 800-1000° C., and the chlorine flow rate is 100 Sccm;

[0072] Step 8: Then, the temperature is raised to vitrify the inner wall of the quartz reaction tube, so that the loose layer on the tube wall condenses quickly, locking the Bi in the pores. 3+ ions, the glass transition temperature is 2200°C, and the pressure in the tube is maintained at 0.8 Torr;

[0073] Step nine, sintering the quartz reaction tube obtained in step eight at 2000-2200° C. into a transparent quartz preform rod;

[0074] Step 10: insert the quartz preform into a sleeve of suitable size and draw it into optical fiber in a drawing tower.

[0075] Embodiment 2:

[0076] Embodiment 2 of the present invention provides a method for preparing a bismuth-doped optical fiber with a high active center concentration. The other steps are the same as those of Embodiment 1, except that the Bi ion concentration in step 2 is 0.6 mol / L, and the Bi ion concentration in step 5 is 0.9 mol / L.

[0077] Comparative Example 1:

[0078] Comparative Example 1 provides a method for preparing a bismuth-doped optical fiber with a high active center concentration. The other steps are the same as those in Example 1, except that there are no steps 4, 5 and 6; at this time, the amount of Bi ion doping is significantly reduced.

[0079] Comparative Example 2:

[0080] Comparative Example 2 provides a method for preparing a bismuth-doped optical fiber with a high active center concentration. The other steps are the same as those in Example 1, except that in step 4, a certain amount of a mixed gas containing oxygen, helium, nitrogen and chlorine, but not containing silicon tetrachloride, is introduced into the tube; at this time, the amount of Bi ion doping is significantly reduced.

[0081] Comparative Example 3:

[0082] Comparative Example 3 provides a method for preparing a bismuth-doped optical fiber with a high active center concentration. The other steps are the same as those in Example 1, except that: the baking temperature in step 4 is 600-800°C, and the chlorine gas flow rate is 100 Sccm; the baking temperature in step 7 is 1400-1600°C, and the chlorine gas flow rate is 100 Sccm; at this time, the Bi ion doping amount is extremely low, and there is no absorption peak of the relevant Bi active center in the absorption spectrum.

[0083] Comparative Example 4:

[0084] Comparative Example 4 provides a method for preparing a bismuth-doped optical fiber with a high active center concentration. The other steps are the same as those in Example 1, except that the nitrogen flow rate in step 3 and step 6 is 100-150 Sccm, the baking temperature in step 4 is 1600-1700°C, and the chlorine flow rate is 100 Sccm; at this time, the Bi ion doping amount is extremely low, and there is no absorption peak of the relevant Bi active center in the absorption spectrum.

[0085] Evaluation test:

[0086] Since the content of bismuth-related active centers in optical fibers is extremely low, exceeding the range limit of conventional testing equipment (such as electron probe microscope EPMA), its accurate content cannot be directly measured. Considering that the absorption peak of the bismuth-related active centers in the optical fiber is located near 1400nm, the content of bismuth active centers in the optical fiber can be indirectly determined by the peak value of the absorption spectrum at 1400nm. The higher the peak value, the higher the content of bismuth active centers.

[0087] See also Figure 2 , Figure 2 The absorption spectra of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are shown. In Comparative Examples 3 and 4, since the Bi ion doping amount is extremely low, there is no absorption peak related to the Bi active center in the absorption spectrum. Figure 2 The relevant absorption spectra are not shown.

[0088] Specifically, in Comparative Example 1, the Bi ion doping amount was significantly reduced because the Bi ion doping process was not performed multiple times.

[0089] Specifically, in Comparative Example 2, before the second Bi ion doping, no loose layer of SiO2 material was deposited, resulting in a significant decrease in the Bi ion doping amount.

[0090] Specifically, in Comparative Example 3, the baking temperature in step 4 is too low, resulting in a decrease in the concentration of Bi ions doped into the loose layer of the SiO2 material; while the baking temperature in step 7 is too high, resulting in most of the Bi ions being volatilized and the concentration of bismuth active centers in the bismuth-doped optical fiber being reduced.

[0091] Specifically, in Comparative Example 4, the nitrogen flow rate in step 3 and step 6 is too large, and the baking temperature in step 7 is too high, which causes most of the Bi ions to be volatilized and reduces the concentration of bismuth active centers in the bismuth-doped optical fiber.

[0092] At present, the absorption value of this type of commercial bismuth-doped optical fiber at 1400nm is only 0.3dB / m. Figure 2 The absorption values ​​of Example 1 and Example 2 at 1400nm are 4.7dB / m and 8.0dB / m respectively, which are significantly higher than the absorption value of commercial bismuth-doped optical fiber, indicating that the preparation method can effectively increase the concentration of bismuth active centers in bismuth-doped optical fiber. In comparison, it can be seen that the absorption of Comparative Example 1 and Comparative Example 2 at 1400nm is only about 0.3dB / m.

[0093] Specifically, the concentration of bismuth active centers in the bismuth-doped optical fiber provided in Example 2 of the present invention is greater than the concentration of bismuth active centers in the bismuth-doped optical fiber provided in Example 1 of the present invention, indicating that appropriately increasing the concentration of Bi ions in the immersion process can effectively increase the concentration of bismuth active centers in the bismuth-doped optical fiber.

[0094] In summary, different from the prior art, the present invention provides a bismuth-doped optical fiber and a preparation method thereof, the method comprising: immersing a quartz reaction tube containing a loose layer in a bismuth-doped optical fiber. 3+ The quartz reaction tube is baked under a first mixed gas to obtain a first dry quartz tube, wherein the first mixed gas includes a mixed gas of silicon tetrachloride, oxygen and chlorine; the first dry quartz tube is immersed in a Bi-containing 3+ The first dried quartz tube is baked under a second mixed gas to obtain a second dried quartz tube, wherein the second mixed gas includes a mixed gas of oxygen and chlorine; the second dried quartz tube is subjected to a vitrification, sintering and drawing process, namely, a bismuth-doped optical fiber; the present invention first immerses the quartz reaction tube containing the loose layer in the first ion solution, so that the Bi in the first ion solution 3+ The Bi is then added into the quartz reaction tube through the pores of the loose layer; the quartz reaction tube is then baked. 3+ While being fixed in the quartz reaction tube, an additional loose layer of SiO2 is deposited on the inner wall of the quartz reaction tube through the reaction of silicon tetrachloride and oxygen; then the first dried quartz tube is immersed in the second ion solution, so that the Bi in the second ion solution 3+The BiO2 is doped into the first dried quartz tube through the pores of the SiO2 loose layer; the first dried quartz tube is then baked to 3+ The bismuth-doped optical fiber is fixed in the first dry quartz tube; finally, the second dry quartz tube is subjected to a vitrification, sintering and drawing process to obtain the bismuth-doped optical fiber; the present invention combines repeated immersion of Bi 3+ The process and corresponding parameters are optimized, and the concentration of Bi-related active centers in bismuth-doped optical fibers is greatly increased without changing or upgrading the existing MCVD conventional preparation conditions. This method is extremely suitable for the existing preparation process system.

[0095] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.

[0096] The above embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing bismuth-doped optical fiber, characterized in that: The following steps are involved: S10, immersing the quartz reaction tube containing the loose layer in a Bi 3+ In the first ion solution; S20, baking the quartz reaction tube under a first mixed gas to obtain a first dried quartz tube, wherein the first mixed gas includes a mixed gas of silicon tetrachloride, oxygen and chlorine; wherein the baking temperature of the baking treatment of the quartz reaction tube under the first mixed gas is 900-1400° C.; S30, immersing the first dried quartz tube in a Bi-containing 3+ in a second ion solution; S40, baking the first dried quartz tube under a second mixed gas to obtain a second dried quartz tube, wherein the second mixed gas includes a mixed gas of oxygen and chlorine; wherein the baking temperature of the first dried quartz tube under the second mixed gas is 800-1000° C.; S50, performing a vitrification, sintering and drawing process on the second dried quartz tube to obtain the bismuth-doped optical fiber; Wherein, in the step S10, the immersion time is 1 to 4 hours, the solvent of the first ion solution is deionized water or anhydrous ethanol, and the solute includes at least Bi 3+ , the first ion solution Bi 3+ The concentration is 0.2-0.6 mol / L; in the step S30, the immersion time is 1-4 h, the solvent of the second ion solution is deionized water or anhydrous ethanol, and the solute includes at least Bi 3+ , the second ion solution Bi 3+ The concentration is 0.5~1.2mol / L; the Bi of the second ion solution 3+ The concentration is greater than that of the first ion solution. 3+ concentration; The step S50 specifically includes: S501, introducing oxygen into the second dry quartz tube and vitrifying the inner wall of the second dry quartz tube, and then sintering to form a transparent quartz preform, wherein the temperature for vitrifying the second dry quartz tube is 1900-2300° C., and the pressure inside the second dry quartz tube during vitrification is 0.6-0.9 Torr; S502, inserting the quartz preform rod into a sleeve, and drawing it into an optical fiber in a drawing tower, namely the bismuth-doped optical fiber; wherein the temperature for shrinking the second dry quartz tube is 2000~2200℃, and the pressure inside the second dry quartz tube during shrinking is 0.1~0.3Torr.

2. The method for preparing bismuth-doped optical fiber according to claim 1, characterized in that: In the step S20, the quartz reaction tube is baked using an oxyhydrogen lamp, and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the first mixed gas in the quartz reaction tube.

3. The method for preparing bismuth-doped optical fiber according to claim 2, characterized in that: In the step S20, the first mixed gas is a mixed gas consisting of silicon tetrachloride, oxygen, helium, nitrogen and chlorine; the flow rate of chlorine in the first mixed gas is greater than 0 and less than or equal to 200 Sccm, and the flow rate of silicon tetrachloride is 100~200 Sccm.

4. The method for preparing bismuth-doped optical fiber according to claim 1, characterized in that: In the step S40, the first dry quartz tube is baked using an oxyhydrogen lamp, and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the second mixed gas in the first dry quartz tube.

5. The method for preparing bismuth-doped optical fiber according to claim 4, characterized in that: The second mixed gas is a mixed gas consisting of oxygen, helium, nitrogen and chlorine; the flow rate of chlorine in the second mixed gas is greater than 0 and less than or equal to 200 Sccm.

6. A bismuth-doped optical fiber, characterized in that: The bismuth-doped optical fiber is prepared by the preparation method of any one of claims 1 to 5.

Citation Information

Patent Citations

  • Three-cladding erbium-ytterbium co-doped optical fiber and preparation method and application thereof

    CN114721087A

  • Erbium-doped optical fiber and preparation method thereof

    CN115411596A